Nano-drug delivery and neuroprotection in spinal cord injury - Sharma H.S.; Ali S.; Tian Z.R.; Patnaik R.; Patnaik S.; Lek P.; Sharma A.; Lundstedt T. (My University, 2025)
Recently nano-drug delivery to the central nervous system (CNS) has been shown to be more effective than the parent compound by itself. An increased availability of the drug for longer periods to the brain or spinal cord and/or a decrease in the drug metabolism altogether could lead to potentiation of the pharmacological activity of the nano-delivered compounds. However, it is still unclear whether the nanocarriers used to deliver the drugs may itself has any potential neurotoxic activity. Although, nanodrug-delivery appears to be a quite promising therapeutic tool for the future clinical therapy, its advantages and limitations for the routine use of patients still needs to be elucidated. Our laboratory is engaged to study a plethora of potential neuroprotective novel compounds delivered to the CNS using nanowiring techniques following brain or spinal cord trauma. Our investigations show that nanowired drugs, if delivered locally following spinal cord injury achieve better neuroprotection than the parent compounds. This effect of nano-drug delivery appears to be very selective in nature. Thus, a clear differentiation based on the compounds used for nano-drug delivery can be seen on various pathological parameters in spinal cord injury. These observations suggest that nanowiring may itself do not induce neuroprotection, but enhance the neuroprotective ability of compounds after trauma. This review describes some recent advances in nano-drug delivery to the CNS in relation to novel neuroprotective strategies with special emphasis on spinal cord trauma based on our own observations and recent findings from our laboratory investigations. Copyright © 2009 American Scientific Publishers.